A Multifaceted Evaluation of National Off-label Neurology Applications - Şükran Yurtoğulları; Hanife Rahmanlar; Ali Alkan; Banu Bayar; Hakkı Gürsöz; Nurten Uzun Adatepe (Türk Nöroloji Dergisi, 2020)
Objective: Off-label drug use (OLDU) of neurologic diseases is approved by a regulatory authority, the Turkish Medicines and Medical Devices Agency (TMMDA) in Turkey. It was aimed to investigate the most common neurologic drugs relevant to off-label prescribing and the most prescribed diagnosis, demographic and medical characteristics of patients with OLDU applications in Turkey. Materials and Methods: Four years “TMMDA”s electronic OLDU application records, 9,758 applications in total, were evaluated retrospectively. Information regarding patients’ demographic characteristics, diagnoses, ordered drugs, and institutions were evaluated. Results: The most OLDU applications were mostly made in 2015, the majority of which were associated with neurodegenerative diseases. The mean age of the patients was 41.6 years and 65% were female. Some 62.1% of off-label drug application patients’ age range was found as 18-64 years. The most common applications were from the Marmara region with 36% and neurology clinics of university hospitals with 81%. Multiple sclerosis (MS) was the most common diagnosis and the most frequently used group of drugs was disease-modifying drugs used in the treatment of MS. Conclusion: Based on the four-year survey of OLDU applications for adult neurologic patients showed that unlicensed drug prescriptions were high. There are very few studies on the result of OLDU applications in neurology worldwide. We believe that this study will be a guide to neurologists with off-label application processes and the results in our country and will make a significant contribution to the literature.